PREDICTION OF FINANCIAL DISTRESS IN INDONESIA FAST MOVING CONSUMER GOODS (FMCG) INDUSTRY - Letizia Neves Pinheiro Lobo Pinto; Pandu Adi Cakranegara (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to find and analyze to prove and test differences in health status results between the Altman Z-Score, Springate, Zmijewski, and Grover. Prediction models in the FMCG Industry for the 2016-2020 period. Samples were taken by the purposive sampling method. Of the 25 listed companies, 16 companies meet the criteria. Data collection techniques collect the required information from the company's financial statements downloaded from www.IDX.co.id. The data analysis technique used is Multiple Discriminant Analysis. The hypothesis test uses the Kruskal Wallis H Test and Accuracy Test. This study indicates that there are differences between the Altman Z-Score, Springate, Zmijewski, and Grover methods in predicting corporate bankruptcy. This can be seen from the probability value of all methods smaller than 0.05, which is 0.00. The accuracy test shows that the methods of Altman, Springate, Zmijewski, and Grover have different accuracy levels, namely 75%, 81%, 97.8%, and 88%, respectively. The high level of accuracy obtained by the Zmijewski methods is 97.8%, respectively. This means that the Zmijewski method is more recommended for companies or investors in assessing the financial condition of manufacturing companies to make decisions. The conclusion is that there are differences between the Altman Z-Score, Springate, Zmijewski, and Grover methods. And the highest accuracy prediction method is the Zmijewski method).